CD24 and CD44 mark human intestinal epithelial cell populations with characteristics of active and facultative stem cells - Gracz, Adam D. (2013)
Recent seminal studies have rapidly advanced the understanding of intestinal epithelial stem cell (IESC) biology in murine models. However, the lack of techniques suitable for isolation and subsequent downstream analysis of IESCs from human tissue has hindered the application of these findings toward the development of novel diagnostics and therapies with direct clinical relevance. This study demonstrates that the cluster of differentiation genes CD24 and CD44 are differentially expressed across LGR5 positive “active” stem cells as well as HOPX positive “facultative” stem cells. Fluorescence-activated cell sorting enables differential enrichment of LGR5 cells (CD24−/CD44+) and HOPX (CD24+/CD44+) cells for gene expression analysis and culture. These findings provide the fundamental methodology and basic cell surface signature necessary for isolating and studying intestinal stem cell populations in human physiology and disease.